Land-use induced changes in extreme temperature predominantly influenced by downward longwave radiation - Meng Zhang; Yanhong Gao; Mingfang Ting; Yan Yu; Guoyin Wang (Communications Earth & Environment)
Abstract Land use is key in regulating surface temperature, yet these relationships are often obscured by long-term mean responses. Here we employed numerical multi-model results to investigate the response of the surface temperature to land use change, especially its lower tails corresponding to boreal winter. The surface temperature decrease in the lower tails can exhibit up to ten times greater than the mean response to land use change over both the historical and future periods. Downward longwave radiation has emerged as the most remarkable contributing factor in controlling surface temperature change in mid-high latitudes of the Northern Hemisphere. Land use change can modify surface energy balance through land-atmosphere firstly, thereby regulate spatial patterns of water vapor and cloud cover in the Northern Hemisphere through teleconnection. The unity of local and remote effects influences the levels of downward longwave radiation and altering surface temperature at mid-high latitudes in extreme cold seasons.